"A Dream Deferred": How Discrimination Impacts the American Dream Achievement for African Americans. (April 2019) - Armstrong, Joslyn; Carlos Chavez, Fiorella L.; Jones, Julia H.; Harris, Shar'Dane; Harris, Gregory J.
The American Dream (TAD) is an ideological symbol of achievement and success in American culture. Historical barriers to equal opportunities and economic attainment through racial discrimination have limited access to TAD for African Americans. Barriers of discrimination also reduce the perception of one's life satisfaction, which can further affect the beliefs of ever obtaining TAD. The present research evaluated the effects of discrimination and life satisfaction on perceptions of achieving TAD among a sample of N = 1, 081 African American adults. Results showed that higher levels of discrimination led to higher odds of African Americans believing that they would never achieve TAD. Income was also significantly associated with TAD attainment, as were age, marital status, and education level. Group differences were found for marital status, age, income, life satisfaction, education, and being worse off financially compared to one's parents. These results support strain theory and racial threat theory by identifying the relationship between discrimination and perceptions of being able to achieve TAD. Those who reported having achieved TAD were more likely to have higher life satisfaction, more successful careers, more financial wealth compared to previous generations, and higher education levels, showing distinct group differences. The study concludes with recommendations for future research into the definition and measurement of TAD and the barriers to attainment for African American families.